2010
DOI: 10.1007/s11743-010-1228-1
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Power in Aqueous Mixtures of Alkylpolyglucosides and Ethoxylated Fatty Alcohols

Abstract: The wetting power of aqueous solutions of mixtures of an ethoxylated fatty alcohol (AE) and an alkylpolyglucoside (AG) and (concentration ratios expressed in dry weight AE:AG = 1:0, 4:1, 3:1, 2:1, 1:2, 0:1) has been evaluated. At low concentrations, the mixtures show better wettability than the pure surfactants. The wettability of mixtures of these surfactants is not significantly influenced by the water hardness or citric acid concentration. Together with the chemical nature of these surfactants, these proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Also, by simple tests, wettability could enable the prediction of behavioral changes of other properties. Thus, for example, some researchers [24] found that the maximum wettability of mixtures of alkylpolyglucosides and ethoxylated alcohols was in agreement with the best detergency results registered in previous works [25,26] with the same surfactant mixtures. Also, surfactant mixtures containing ethoxylated alcohols have been used to improve the wetting power of other pure surfactants separately.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, by simple tests, wettability could enable the prediction of behavioral changes of other properties. Thus, for example, some researchers [24] found that the maximum wettability of mixtures of alkylpolyglucosides and ethoxylated alcohols was in agreement with the best detergency results registered in previous works [25,26] with the same surfactant mixtures. Also, surfactant mixtures containing ethoxylated alcohols have been used to improve the wetting power of other pure surfactants separately.…”
Section: Introductionsupporting
confidence: 88%
“…Previous works [24] also found a synergistic effect in wettability with the EA-C 12-14 -OE 11 when this surfactant was in the presence of certain alkylpolyglucosides. The mixtures EA-C 12-14 -OE 11 : alkylpolyglucosides also improved other properties such as efficiency in the cleaning of hard surfaces [8].…”
Section: Wettability Of Aqueous Solutions Of Pge Surfactantsmentioning
confidence: 71%
See 1 more Smart Citation
“…[35] The ease with which a surface can be wetted by water or by other liquid is an important property from many considerations, including textile processing, dyeing, and detergency. The requirement of a wetting agent is evidently to reduce the surface tension of liquid.…”
Section: Wettingmentioning
confidence: 99%
“…Although very useful for surface characterization, the contact angle is not the cause of wetting but a consequence of it [3]. Jurado et al [6,7], analyzing the wetting power and the detergency of aqueous solutions of mixtures of APG and ethoxylated fatty alcohols, observed that the most favorable surfactant formulation for hardsurface cleaning coincided with the composition that provided the highest wetting power [8]; moreover, these formulations improved triolein solubilization compared to the pure surfactants [9]. Perhaps the most widely used test for evaluating the wetting power of surfactant is the Draves wetting test [4].…”
Section: Introductionmentioning
confidence: 99%